2020
DOI: 10.1101/2020.04.17.047167
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structured sampling of olfactory input by the fly mushroom body

Abstract: 15Associative memory formation and recall in the adult fruit fly Drosophila melanogaster is 16 subserved by the mushroom body (MB). Upon arrival in the MB, sensory information undergoes 17 a profound transformation. Olfactory projection neurons (PNs), the main MB input, exhibit 18 broadly tuned, sustained, and stereotyped responses to odorants; in contrast, their postsynaptic 19 targets in the MB, the Kenyon cells (KCs), are nonstereotyped, narrowly tuned, and only briefly 20 responsive to odorants. Theory and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 132 publications
(173 reference statements)
6
58
1
Order By: Relevance
“…First, although olfactory input to the KCs is highly mixed, various structural features reduce the dimensionality of the KC odor representation. A recent analysis of EM data from an adult Drosophila MB identified groups of PNs thought to represent food odors that are preferentially sampled by certain KCs (Zheng et al, 2020). Consistent with this observation, our analysis revealed subtype-specific biases in PN sampling by KCs, including an overrepresentation of specific glomeruli by α/β and α′/β′ KCs.…”
Section: Sensory Input To Kcssupporting
confidence: 85%
See 2 more Smart Citations
“…First, although olfactory input to the KCs is highly mixed, various structural features reduce the dimensionality of the KC odor representation. A recent analysis of EM data from an adult Drosophila MB identified groups of PNs thought to represent food odors that are preferentially sampled by certain KCs (Zheng et al, 2020). Consistent with this observation, our analysis revealed subtype-specific biases in PN sampling by KCs, including an overrepresentation of specific glomeruli by α/β and α′/β′ KCs.…”
Section: Sensory Input To Kcssupporting
confidence: 85%
“…This maintained segregation is most prominent for α′/β′ KCs but is also seen in α/β KCs ( Figure 5E-G). The dendrites of each KC type also tend to be found in the same region of the CA (Video 6; Leiss et al, 2009;Lin et al, 2007;Zheng et al, 2020), which, in some cases, appears to support input specialization. These features of the spatial mapping from CA to lobes and the organisation of the parallel fiber system presumably evolved to facilitate associative learning.…”
Section: Kcs: the Major Mb Intrinsic Neurons And Conveyors Of Sensorymentioning
confidence: 78%
See 1 more Smart Citation
“…Some food-related odor channels may directly facilitate the action of others. A new study observed a community of PNs in the MB CA, a food-related “associational fovea”, densely sampled by a population of KCs [ 68 ]. This community is almost identical to the food-related, axo-axonic community we observe in the LH (note that both studies use the same EM data).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we compare and validate results using a second EM data set, the full adult fly brain (FAFB, (Zheng et al, 2018)), which has been used until now for sparse manual circuit tracing (e.g. (Dolan et al, 2018; Dolan et al, 2019; Sayin et al, 2019; Felsenberg et al, 2018; Huoviala et al, 2018; Zheng et al, 2020; Marin et al, 2020; Bates et al, 2020; Otto et al, 2020; Coates et al, 2020)).…”
Section: Introductionmentioning
confidence: 95%